Lexical Nominations as Indices of Educational and Social Status - T. A. Ivushkina (Научный диалог)
Lexical units, that index the educational status of graduates of Oxbridge and are included in the dictionary of representatives of the upper classes of Great Britain, are considered. The identification of U-words is based on the analysis of “The Fry Chronicles” (2010) by Stephen Fry, a well-known actor, writer and publicist, a graduate of the University of Cambridge. The material and the approach to identification of socially-marked vocabulary determines the novelty of the study. The author proceeds from the fact that the scientific interest in the manifestation of social status in a language still does not lose its relevance. The universities of Oxford and Cambridge stably maintain the status of the most prestigious universities according to QS University Ratings, not only in their own country, but also far beyond its borders. In “The Chronicles”, Stephen Fry provides an opportunity to follow the nuances of the use of certain lexical nominations in the student and teaching environment of the University of Cambridge and partly Oxford. The lexical units, which form the following thematic fields: (1) university, (2) teachers and employees; (3) students and exams are distinguished. It is stated that words of Latin origin mark the speech of the upper classes, creating a certain social distance, and borrowings from the German language replenish student slang.